2019
DOI: 10.1172/jci.insight.132826
|View full text |Cite
|
Sign up to set email alerts
|

Mitophagy-dependent macrophage reprogramming protects against kidney fibrosis

Abstract: The spouse of MEC is a cofounder and shareholder and serves on the Scientific Advisory Board of Proterris Inc. AMKC is a cofounder and stockholder and serves on the Scientific Advisory Board for Proterris, which develops therapeutic uses for carbon monoxide. AMKC also has a use patent on (no. 7,678,390) carbon monoxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
93
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(102 citation statements)
references
References 52 publications
2
93
0
Order By: Relevance
“…Emerging evidence suggests that mitochondrial dysfunction is also a key contributor to the pathogenesis of CKD. Mitochondrial structural and functional impairments are increasingly recognized as critical mediators of many kidney diseases [12,20,56]. Here, we summarize recent advances in unraveling the functional significance of mitochondrial dysfunction in promoting inflammation and fibrotic responses in the pathogenesis of tubulointerstitial fibrosis (TIF) and various forms of CKD, including diabetic nephropathy (DN), IgA nephropathy (IgAN), membranous nephropathy (MN), and polycystic kidney disease (PKD).…”
Section: Mitochondrial Dysfunction In Chronic Kidney Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Emerging evidence suggests that mitochondrial dysfunction is also a key contributor to the pathogenesis of CKD. Mitochondrial structural and functional impairments are increasingly recognized as critical mediators of many kidney diseases [12,20,56]. Here, we summarize recent advances in unraveling the functional significance of mitochondrial dysfunction in promoting inflammation and fibrotic responses in the pathogenesis of tubulointerstitial fibrosis (TIF) and various forms of CKD, including diabetic nephropathy (DN), IgA nephropathy (IgAN), membranous nephropathy (MN), and polycystic kidney disease (PKD).…”
Section: Mitochondrial Dysfunction In Chronic Kidney Diseasementioning
confidence: 99%
“…The GTPase activity of MFN1 is higher than that of MFN2, and OPA1 fails to execute the process of mitochondrial fusion in the absence of MFN1 [9,10]. MFN2, on the other hand, regulates mitophagy [11,12]. MFN2 also facilitates tethering and interaction between mitochondria and the endoplasmic reticulum (ER) at mitochondria-associated membranes (MAMs) and maintains efficient calcium (Ca 2+ ) uptake by mitochondria [13].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that phosphatase and tension homologue (PTEN)-induced kinase 1/ (PINK1)/mitofusion 2 (MFN2)/Parkin-mediated macrophage mitophagy is downregulated during kidney fibrosis, and loss of either Pink1 or Parkin promoted macrophage development toward profibrotic/M2 macrophages and subsequent renal fibrosis [50]. Additionally, autophagy induced by the histone deacetylase inhibitor, valproic acid, suppressed renal fibrosis in mice subjected to UUO [51].…”
Section: Autophagy In Renal Interstitial Fibrosis and Progressive Kidmentioning
confidence: 99%
“…More recently, Bhatia et al report that PINK1-MFN2-PARK2 pathway of mitophagy in macrophages was compromised in experimental and human kidney fibrosis. Failure of this pathway of mitophagy resulted in accumulation of abnormal mitochondria, increased mtROS production, and increased RICTOR (RPTOR independent companion of MTOR complex 2) expression in macrophages, which in turn promoted the differentiation of macrophages toward profibrotic/M2 phenotype, leading to higher extracellular matrix production and progression of kidney fibrosis in UUO mice, suggesting that PINK1-MFN2-PARK2-mediated mitophagy in macrophages plays an anti-fibrotic role in kidneys [131]. Collectively, these findings suggest that mitophagy in renal tubular cells facilitates renal repair.…”
Section: Mitophagy In Kidney Repair and Renal Fibrosismentioning
confidence: 99%